COMPARATIVE ANALYSIS OF CONTINENTAL AND OCEANIC PLATEAU BASALTS (DATA ON THE SIBERIAN PLATFORM AND ONTONG JAVA PLATEAU) - Zolotukhin V.V.; Simonov V.A.; Al'mukhamedov A.I.; Medvedev A.Ya.; Vasil'ev Yu.R. (My University, 2003)
Previous research has shown that the sections of the vast volcanogenic trap field of the Siberian Platform bear analogs of oceanic A- and C-G-type plateau basalts. Comparative analysis of volcanic rocks shows that basalts of the Siberian Platform and the Ontong Java Plateau have similar compositions and differ considerably in them from MOR rocks. This suggests that the geodynamic processes that formed great volumes of magmas in the former two provinces were similar and differed from the deep-level processes that occurred beneath MOR. Basalts of both the Siberian Platform and the Java Ontong Plateau might have resulted from the ascent of huge plumes that acted, most likely, by the mechanism of huge "drops" pulled apart from the feeding source.
Keywords: Plateau basalts; Siberian Platform; Ontong Java Plateau; Nauru basin